Intimate Interfacial Interaction between Amino‐Modified Ti5 Clusters and BiVO4 towards Efficient Photoelectrochemical Water Splitting. Issue 9 (14th June 2019) - Dai, Shuqi; Jiang, Lizhi; Zhao, Chaowei; Chen, Fengjiao; Chen, Ruihao; Qin, Ruixuan; Zhang, Wuyong; Zhang, Weijie; Wu, Binghui; Zheng, Nanfeng
Abstract: In this work, a novel series of amino‐modified Ti5 clusters (NH2 ‐TOCs) with a Janus surface were synthesized. Then, a facile hydrolysis self‐assembly strategy was adopted to fabricate a well‐defined monolayer of NH2 ‐TOCs on BiVO4 with intimate interaction at low temperature. The as‐formed NH2 ‐TOCs/BiVO4 heterojunction electrode exhibited high performance on photoelectrochemical water‐splitting, which was ascribed to strong M−O−Ti (M=Bi, V) bonding at the interface. It is anticipated that this work could boost new insights for cluster‐support interaction and corresponding applications. Abstract : Amino‐modified Ti5 clusters and BiVO4 film were used to form a well‐defined BiVO4 /cluster heterostructure with strong Ti−O−M (M=Bi, V) chemical bonding via a facile hydrolysis self‐assembly strategy. The as‐prepared BiVO4 /cluster electrode with intimate Ti−O−M interface exhibited significantly improved photoelectrochemical water‐splitting, superior to the counterpart BiVO4 /TiO2 or bare BiVO4 .